Historical trends of trace metals in muddy deposit along the Zhejiang coast, East China Sea: response to economic development and hypoxia - Xu, G.; Liu, Jian; Dou, Y.; Qiu, J.; Chen, L. (Springer, 2018)
© 2017, Springer-Verlag GmbH Germany. One sediment core spanning approximately 138 years was taken from the muddy deposits along the Zhejiang coast of the East China Sea, which is located in a hypoxic zone south of the Yangtze River estuary. When the sources of the trace metals in the core were analyzed, the three geochemical sources were identified as lithogenic, anthropogenic, and reductive deposits based on both principal component analysis and the ratios of terrigenous elements. The temporal distribution of the enrichment factor of copper in the sediment core matches the timeline of economic development and national policy in China. The rapid increase in human activity and economic development in the Yangtze River catchment accounts for the enrichment of copper in the sediment core. Based on the vertical distribution of arsenic concentration, the hypoxic zone south of the Yangtze River estuary may have not only existed, but worsened since 1875.